Sexual Dysfunction Reduction in Female Patients with Chronic Kidney Disease Undergoing Continuous Ambulatory Peritoneal Dialysis - Gede Wirya Kusuma Duarsa; Yenny Kandarini; Luciana Luciana; Ida Bagus Putra Pramana; Gede Wirata; Pande Made Wisnu Tirtayasa; I Wayan Yudiana; Kadek Budi Santosa; Anak Agung Gde Oka (Interna Publishing, 2020)
Background: chronic kidney disease (CKD) is a major worldwide health problem. One key treatment for end-stage CKD patients is dialysis therapy such as Continuous Ambulatory Peritoneal Dialysis (CAPD). This study aimed to find out the differences in the incidence of sexual dysfunction in women with CKD by CAPD. Methods: this study was a multicenter observational analytic study design in female samples before CAPD and after CAPD. It was conducted between November 2018 - January 2019 with 26 female respondents. They were assessed using the Female Sexual Function Index (FSFI) questionnaire at pre-CAPD and post-CAPD. Results: the results of the FSFI score before CAPD were 32.77 (SD 19.72) and after CAPD was 48.88 (SD 20.29). Analysis of differences in FSFI scores before and after CAPD demonstrates that there was a significant difference (p = 0.003). Conclusion: women with CKD who underwent CAPD, had an increase in FSFI scores compared to before CAPD. Thus, the use of CAPD can be seen to reduce sexual dysfunction and therefore improve the quality of life of women with CKD.